Quantification of climate-tourism potential for Athens, Greece - Recent and future climate simulations - Matzarakis, A.; Endler, C.; Nastos, P. T. (Global Nest Journal, 2014)
The aim of this paper is to present in a useful and understandable way how climatic change could be interpreted for tourism and recreation. Future climate change conditions are analyzed using the Climate Version of the Local Model (CLM) based on the COSMO model, which is currently used-among other weather services-by the DWD (Deutscher Wetterdienst) for operational weather forecast. The climate simulations concern the future periods 2021-2050 and 2071-2100 against the reference period 1961-1990, under A1B scenario. Based on regional climate simulations, the analysis for tourism can be performed using the Climate-Tourism-Information-Scheme (CTIS). The CTIS contains detailed climate information, which can be used by tourists to anticipate thermal comfort, aesthetical and physical conditions for planning their vacations. Furthermore, the Physiologically Equivalent Temperature (PET), which is one of the most popular physiological thermal indices derived from the human energy balance, is used in the analysis in order to describe the effect of climate. The future simulations concerning PET and CTIS for the area for Athens have been exemplary used, in order to consider them for tourism industry and local authorities for tourism planning. © 2014 Global NEST Printed in Greece. All rights reserved.
Keywords: Athens; Climate and tourism; Climate-tourism-information-scheme; CLM; Physiologically equivalent temperature